Coaching analítico-comportamental: estudos sobre efetividade de coaching feito por um analista do comportamento - Borges, Nicodemos Batista (2015)
Coaching has been a growing intervention practice in Brazil and worldwide. Despite the increase in demand for this service, there are few researches to ground this practice. Behavior Analysis is a multidimensional field of knowledge, which object of study is behavior. It has well developed body of basic and advanced research and theoreticalphilosophical axis, and it has also produced a set of technologies for behavioral change. This thesis aims, in general, to discuss and this intervention practice through the optical lens of Behavior Analysis. More specifically, the thesis consists of a brief discussion of coaching and behavior analysis and presentation of three studies. Study 1 aimed to discuss the effectiveness of coaching using traditional measurements (scales and inventories), but using single subject design, respecting tradition in Behavior Analysis when delineating studies. Also, a second goal was to verify the effectiveness of the To do technique/tool, often used by those who work with coaching. Study 2 is a case study aimed to verify the effectiveness of coaching, conducted by a behavior analyst, to develop and/or maintain behaviors which prepare the individual for retirement, as in having career plans, financial reserve, care for relationships which can support her in old age (such as family, emotional and social relationships) and health care. Study 3 is a case study aimed to assess the effectiveness of coaching, conducted by a behavior analyst, to develop autonomy of thought or the Tracking kind of behavior. These studies had as participant two clients who were looking for coaching service, one behavior analyst coaching professional, and an external observer. The interventions consisted of ten individual coaching meetings for each client. In such meetings, the objectives of each client were discussed and individualized interventions were performed in order to handle contingencies that established and/or maintained behaviors related to coaching objectives. To measure result, different measurement were used, from conventional such as scales and inventories (e. g. BDI, STAI, etc.) to direct measurements of the evolution of behavior occurring during coaching meetings. The results of the studies indicated that coaching conducted by an behavior analyst was effective for both clients irrespective of the means of measurement used, both if resorting to comparison of results of traditional scoring instruments obtained before and after coaching (Study 1), as through measurements derived from direct observations. The interventions were effective in promoting both the engagement for retirement (Study 2) and the freedom of thought (Study 3). In addition, Study 1 presents evidence that the To the technique /tool is effective in evoking behaviors related to coaching objectives, that is, commitment